Influence of the Textural Parameters of LDH-TiO2 Composites on Phenol Adsorption and Photodegradation Capacities - J. C. Contreras-Ruiz; S. Martínez-Gallegos; J. L. García-Rivas; J. Illescas; J. C. González-Juárez; Guadalupe Macedo Miranda; Eduardo Ordoñez Regil (International Journal of Photoenergy, 2019)
Layered double hydroxides (LDH) M2+M3+CO32− were synthesized following the sol-gel methodology using Mg-Al, Mg-Fe, and Zn-Al as cation pairs for subsequent use in the preparation of TiO2/LDH materials. The samples were characterized by infrared spectroscopy (IR), scanning electron microscopy (SEM), and the Brunauer–Emmett–Teller (BET) technique to determine the surface area (SA); the results of which were used to determine the roughness of the samples in terms of surface fractal dimension (D). The prepared materials exhibited both adsorption and photocatalytic properties in the removal of phenol in aqueous solution under ultraviolet irradiation. This work studies the relationship between the textural parameters of the materials obtained in relation to their photocatalytic efficiency and adsorption capacity, finding that the surface of the solids, their structural heterogeneity, and roughness condition the photodegradation and adsorption processes, using phenol as reference organic pollutant. The results show that different cation in LDH influences in photocatalytic capacity; the TiO2/ZnAl was the best material in one test, but after 10 times of test, the TiO2/MgFe gave the better photodegradation material. In adsorption capacity, TiO2/ZnAl and TiO2/MgFe have a close rate for phenol adsorption and both were better than TiO2/MgAl. The differences in textural characteristics (surface area, surface roughness, and pore-size distribution) affected phenol adsorption and photodegradation efficiency.